ESTIMATE GESTATIONAL AGE ACCORDING TO FETAL CROWN RUMP LENGTH ON ECHOGRAPHY (Vietnam Journal of Community Medicine, 2021)
Objectives: Development of descriptive table of gestational age (GA) based on fetal crown rump length (CRL) in Vietnam. Methods: This study was conducted at the Center for Prenatal Diagnosis, National Hospital Obstetrics and Gynecology. Gestational age based on the first day of last menstrual period (LMP) ranges from 10 weeks to 14 weeks and 6 days. Pregnant women who are healthy, have regular menstrual periods, have not used hormonal drugs or assisted reproductive methods before. Have ultrasound measured the length of the crown-rump of the embryo based on the mandatory criteria. Data were analysed using SPSS 20.0 software. Results: 1008 singleton fetuses that met criteria, were predicted GA according to LMP. There were 1008 fetal crown rump length recorded. The mean CRL was 59.95 ± 6.79 (mm), the mean gestational age according to KCC was: 12.13 ± 0.75 (weeks). Gestational age was linearly correlated with fetal crown rump length according to the equation: CRL = 6.602+ GAx 4.398 and GA= 8.889 + CRLx 0.54. Conclusion: Gestational age can be calculated based on fetal crown rump length index by linear equation: GA = 8.889 + CRLx 0.54. The equations can be applied to calculate gestational age in ultrasound practice in Vietnam.
Keywords: Crown rump length, last menstrual period, gestational age